Propuesta de mejora de los puestos de trabajo de la empresa Corporación LUDIEVI SAC para aumentar la productividad - Vasquez Paredes, Damaris Marly (2024)
The present investigation was carried out in the company Corporación LUDIEVI SAC with the objective of increasing productivity through the proposal of improvement in the work stations. To this end, an analysis of the production process was carried out using various ergonomic tools such as the REBA method where the result showed that workers in the workstations have a high and very high level of risk of having musculoskeletal disorders, also the results of an IPERC matrix showed a moderate, important and intolerable level of risk; on the other hand, through the ergonomic checklist it was evaluated that the company did not comply with 56 of 65 items. Finally, noise measurements showed that the noise exceeded what was allowed by the standard, with a sound pressure level calculation of 100,57 dB. As a result, a proposal was made to design the workstations to mitigate these problems, including ergonomic chairs, work tables, conveyor carts, ear protectors and a program of active breaks. As a result, a 30% increase in labor productivity and manpower was noted, as well as a reduction in noise. The financial analysis demonstrated the feasibility of the project with a Net Present Value (NPV) of S/11 350,70, an Internal Rate of Return (IRR) of 33% and a benefit-cost ratio of 1,39.